IMPACTO DA COVID-19 EM FRÁGEIS ATORES DA CADEIA DE SUPRIMENTOS CIRCULAR E OS OBJETIVOS DO DESENVOLVIMENTO SUSTENTÁVEL - Cerqueira Streit, Jorge Alfredo; Guarnieri, Patrícia; Batista, Luciano; Alfinito, Solange (Revista Gestão Organizacional, 2023)
Purpose: This paper aims to analyse the human and work situation of waste pickers in the federal capital of Brazil (Distrito Federal) during the COVID-19 pandemic, connecting them to the Sustainable Development Goals. Method/approach: We conducted a descriptive case study using a qualitative approach when interviewing ten leaders of their organisations. Following content analysis technique, we created nine thematic categories to understand the waste pickers' perception of stakeholder participation, besides the challenges and opportunities in the three dimensions of sustainability: social, environmental and economic. Main findings: During the COVID-19 pandemic, waste pickers' organisations in the Distrito Federal had their operations wholly paralysed for six months. The government's participation was negative because of the delay in financial assistance and conflicting information, and some private companies provided support. Due to donations of food and hygiene products, society was the stakeholder that most recognised the importance of work and the vulnerability of the waste picker. We discussed the results from the perspective of Sustainable Development Goals to list the risks and opportunities of this period. Theoretical, practical/social contributions: Theoretically, this article contributes by demonstrating categories for analysing the perception of stakeholders. Public and private agents can use its results to adjust their practices in search of SDGs. Finally, the paper's social importance is providing information about these workers' vulnerability and their role in making the solid waste chain more circular. Originality/relevance: This paper is distinguished from the others because, so far, there are no articles in the Brazilian literature that relate the themes of the COVID-19 pandemic and the work of waste pickers to achieve Sustainable Development Goals.